2015
DOI: 10.5194/bgd-12-16645-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactive effects of and light on growth rates and RUBISCO content of small and large centric diatoms

Abstract: <p><strong>Abstract.</strong> Among marine phytoplankton groups, diatoms span the widest range of cell size, with resulting effects upon their nitrogen uptake, photosynthesis and growth responses to light. We grew two strains of marine centric diatoms, the small <i>Thalassiosira pseudonana</i> and the larger <i>T. punctigera</i> in high and low nitrogen media, across a range of growth light levels. Nitrogen and total proteins per cell decreased with increasing growth l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Although the dark reactions of photosynthesis were probably limiting at high irradiance, cells did not compensate by increasing Rubisco content. Rubisco contents measured in this study (5-18% of total protein) are higher than the majority of the values reported for mesophilic diatoms [41][42][43] (see grey line in Fig 3) but accord well with those of psychrophilic diatoms (17% of total protein) [3].…”
Section: Rubiscosupporting
confidence: 82%
“…Although the dark reactions of photosynthesis were probably limiting at high irradiance, cells did not compensate by increasing Rubisco content. Rubisco contents measured in this study (5-18% of total protein) are higher than the majority of the values reported for mesophilic diatoms [41][42][43] (see grey line in Fig 3) but accord well with those of psychrophilic diatoms (17% of total protein) [3].…”
Section: Rubiscosupporting
confidence: 82%